Nasruddin Umar's Love Curriculum And Its Relation To Arabic Language Teaching: Socio-Linguistic And Semantic Studies/ منهج الحب عند نصر الدين عمر وعلاقته بتعليم اللغة العربية: دراسات اجتماعية لغوية ودلالية - Pallawagau, Baso; Masuwd, Mowafg; Alsayd, Abdulnasir Dhaw; Albshkar, Hajer Abdallah; Alzletni, Naima Salem (Ijaz Arabi Journal of Arabic Learning, 2025)
Love is a universal concept that has captivated philosophers and thinkers across different eras and cultures. Nasaruddin Umar, as a contemporary Islamic thinker, offers a comprehensive perspective on love through his concept known as the Curriculum of Love. This research aims to reconstruct the meaning of love based on Nasaruddin Umar’s Curriculum of Love using a socio-linguistics semantic approach, focusing on the linguistics and social meanings embedded within this concept. This research employs a descriptive-analytical method by semantically analyzing the narrative of “LOVE” in Nasaruddin Umar’s Curriculum of Love to reveal the domains of meaning contained within the concept of love. Furthermore, the research explores the social and cultural dimensions shaping this concept from a socio-linguistic perspective. This research examines fundamental issues such as the relationship between love and Arabic language education, the correlation between spiritual and emotional aspects, and the extent to which cultural and social contexts influence this theory. The findings indicate that Nasaruddin Umar redefines love as a holistic condition that transcends mere emotional dimensions to encompass spiritual, ethical, social, and educational aspects. Additionally, his language reflects an integration of Islamic Sufi heritage with modern concepts, making his ideas a synthesis of traditional and contemporary thought. Through socio-linguistics analysis, it is found that the cultural context of Islam influences the concept of love in Nasaruddin Umar’s theory and embodies values of tolerance, compassion, and harmony in interpersonal and societal relationships. According to this theory, this research concludes that love is not merely an individual emotion but also an epistemological and ethical system that plays a vital role in constructing human and social relationships based on mutual understanding and respect. This research recommends further studies to explore other dimensions of the Curriculum of Love within various philosophical and religious contexts to enrich the understanding of love in contemporary thought.